Effect of glycosaminoglycan (GAGs) extract from local Malaysia sea cucumber Stichopus vastus on inflammatory mediators and tissue healing on rodents with full thickness burn injury - Mohd Faeiz Pauzi
Titile: EFFECT OF GL YCOSAMINOGL YCAN (GAG) EXTRACT FROM MALAYSIA SEA CUCUMBER STICHOPUS VASTUS ON INFLAMMATORY MEDIATORS AND WOUND HEALING ON RODENTS WITH FULL TIDCKNESS BURN INJURY Introduction: Invertebrate like sea cucumbers have been long used in traditional medicine and having various nutritional and medicinal value added properties especially for wound healing. This may be due to the presence of sulfated gylocasminoglycans (GAGs). The aim of this study was to investigate the effect of total sulfated GAG from body wall of local Malaysia sea cucumber Stichopus vastus on inflammatory mediators and tissue healing on rodents with full thickness burn injury. Objectives: To characterize, elucidate, and observe level of inflammatory mediators and wound healing activity between burn wound of rodents receiving treatment with total sulfated AG from Stichopus vastus and without treatment. Methodology: The content of total sulfated GAG was measured from integument wall of sea cucumber species. Twelve male Sprague-dawley rats weighting between 350-400 grams were used. The animals were distributed at random into two groups of six animals; treated with sulfated GAG from S. vastus and control group. Full thickness burn wounds were created. Six rats in group A received 5 ml/kg/day intraperitoneal total sulfated GAG for 5 days, while control group, group B received phosphate buffered saline (PBS). Evaluation of blood level of inflammatory mediators IL-IO and IL-12 at day 1 as baseline and followed by measurement at day 6 and 12. All rats of each group were euthanized at day 12 and the tissue biopsies from the wounds were retrieved for histological examination.Result: The level of IL 10 revealed significantly (p=0.001) higher in sulfated GAG treated group on each observation from baseline (8.02±0.14) up to [day 6 (11.78±0.72) and day 12 (13.61±0.79)] compared to control group [day 1 (8.11±0.06), day 6 (8.55±0.28) and day 12 (8.88±0.42)]. The level ofIL 12 was reduced significantly (p=O.OOI) in sulfated GAG treated group from baseline (1155.54±9.56) up to day 6 (1036.34±32.94) and day 12 (919.09±72.03) observation period compared to control group [day 1 (1150.53±22.85). day 6 (1273.91±68.38) and day 12 (1340.71±73.37)]. Data suggested that sulfated GAG from S vastus integument body wall increase anti-inflammatory cytokine and reduce proinflammatory cytokine.Microscopic evaluation was done on day 12. The epithelial migration progress of treated group was not significant (p=0.599) compared to control group. However for inflammatory cells evaluation showed reduced neutrophils infiltration (p=O.OOl) with enhanced proliferation of fibroblasts (p=0.017) and increase in new vessels formation (p=0.001) in the sulfated GAG treated group compared to control group.Conclusion: In this study we have demonstrated that sulfated GAG from S va tus integument body wall has impact on the outcome of wound healing process. Thus, intraperitoneal injection of sulfated GAG increase the level of anti inflammatory cytokine, IL 10 and reduced level of pro-inflammatory cytokine, IL 12. As shown in this dissertation, sulfated GAG seems to hasten the wound healing event through positive effect on fibroblast proliferation and angiogenesis process. Keywords: Glycosaminoglycan (GAG), sea cucumber, Stichopus vastus, inflammatory mediators